Compensation in the Termination of Agreement Due to Breach of Contract - Al Hafiz, M.; Sukirno, Sukirno (International Journal of Multi Discipline Science (IJ-MDS), 2024)
In the execution of an agreement, there are cases where parties are unable to fulfil their rights and obligations as agreed, resulting in a breach of contract, known as "wanprestasi" in Indonesian law. Breach of contract can be a cause for terminating the agreement, as stipulated in Article 1266 of the Civil Code (Kitab Undang-Undang Hukum Perdata). The termination of an agreement due to a breach of contract has legal consequences, and the parties involved can claim their rights resulting from the cancellation, including the right to seek compensation for the losses suffered. This research aims to examine the compensation for the termination of an agreement due to a breach of contract. This research was a doctrinal law research based on a literature study. The approach method used in this research was the statute approach. In cases where an agreement is terminated due to breach of contract, the aggrieved party can file a claim for compensation, which includes costs (konsten), losses (schaden), and interest (interessen). However, the aggrieved party cannot claim compensation if the breach of contract occurred due to force majeure or unforeseen circumstances.